PENITENTIARY CORRUPTION: CRIMINOLOGICAL AND PENAL ASPECTS - L. B. Smirnov (Теоретическая и прикладная юриспруденция)
The article discusses the features of corruption crime in places of detention. The subjects of corruption relations in the penitentiary sphere are shown. The problems of prevention and combating penitentiary corruption are presented. Based on the analysis, measures to counter corruption manifestations in correctional institutions are proposed.